Effects Of Water Quality On Periphyton In The Pattani River, Yala Municipality, Thailand [TD370. V634 2008 f rb]. - Rangpan, Vichit (2008)
Data collection and field surveys were carried out from March 1999 to February 2000 to study the effects of water quality on the periphyton populations in the Pattani River.